Jenis- Jenis Serangga yang Ditemukan Di Ekosistem Sawah Di Desa Juhut Kabupaten Pandeglang - Jasmi, Riski Andrian; Febryansyah, Azmy; Musthopa, Muhammad Huda; Hanafiah, Raihan Imam; Hikmah, Azeng Nurul; Laira, Miftahul (Symbiotic: Journal of Biological Education and Science, 2025)
Rice fields are ecosystems that are home to various types of insects that play roles as herbivores, predators, pollinators, and decomposers. This study aims to analyze the various types of insects found in the rice fields of Juhut Village, Pandeglang Regency. The research method used is qualitative, with data collection using random sampling. Data analysis was performed using descriptive qualitative analysis. A total of 137 insect individuals were found, consisting of pest insects, pollinating insects, soil insects, and predatory insects. The identified insects came from the order Orthoptera (Valanga nigricornis, Atractomorpha crenulata, and Gryllus testaceus) at 25.55%, Hemiptera (Leptocorisa acuta, and Bemisia tabachi) at 43.80%, Lepidoptera (Leptosia nina, Phaedyma columella, Hypolimnas bolina, Catopsilia Pomona, Graphium Agamemnon, and Papilio memnon) at 9.49%, Odonata (Neurothemis fluctuans, Diplacodes trivialis, Tramea transmarina, Agriocnemis femina, and Orthetrum sabina) at 17.52%, and Coleoptera (Coccinella sp.) at 3.65%. This study shows that rice field ecosystems have a fairly high level of insect species, which play a major role in the balance of rice field ecosystems.